Frozen in Time: Intraoperative Diagnosis and Management of Malignant Transformation in Mature Cystic Teratoma - Arun Sudhakar Sanap; Medha D. Davile; Anusha A. Kamath; Shuchita R. Mundle (Wolters Kluwer Medknow Publications, 2024)
Malignant transformation (MCT) of ovary is rare complications affecting elderly, squamous cell carcinoma being the most common. The prognosis worsens with extraovarian spread. We present two cases of MCT-derived SCC. Patients exhibited abdominal lump, pain, bowel symptoms, sometimes with weight loss; imaging revealed MCT. Age (51-60), postmenopausal status, large size (>20 cm), bilaterality, and complex ovarian lesions raised suspicion of malignancy. Elevated tumor markers (e.g., cancer antigen-125 and lactate dehydrogenase) were noted in one case. Intraoperative frozen section confirmed malignancy, guiding staging laparotomy. One case was advanced stage on histopathology. Intraoperative frozen section aids optimal staging.